beyond Fear - Bruce Schneier (COPERNICUS BOOKS, 2003)
In the wake of 9/11, many of us want to reinvent our ideas about security. But we don’t need to learn something completely new; we need to learn to be smarter, more skeptical, and more skilled about what we already know. Critical to any security decision is the notion of trade-offs, meaning the costs—in terms of money, convenience, comfort, freedoms, and so on—that inevitably attach themselves to any security system. People make security trade-offs naturally, choosing more or less security as situations change. This book uses a five-step process to demystify the choices and make the trade-offs explicit. A better understanding of trade-offs leads to a better understanding of security, and consequently to more sensible security decisions